Endocytosis, Cytotoxicity, and Translocation of Shiga Toxin-2 Are Stimulated by Infection of Human Intestinal (HCT-8) Monolayers With an Hypervirulent E. coli O157:H7 Lacking stx2 Gene - Garimano, Nicolás; Amaral, María Marta; Ibarra, Cristina (Frontiers in Cellular and Infection Microbiology, 2019)
Shiga toxin-producing Escherichia coli (STEC) strains are responsible for multiple clinical syndromes, including hemolytic uremic syndrome (HUS). E. coli O157:H7 is the most prevalent serotype associated with HUS and produces a variety of virulence factors being Stx2 the responsible of the most HUS severe cases. After intestinal colonization by STEC, Stx2 is released into the intestinal lumen, translocated to the circulatory system and then binds to its receptor, globotriaosylceramide (Gb3), in target cells. Thus, Stx2 passage through the colonic epithelial barrier is a key step in order to produce disease, being its mechanisms still poorly understood. We have previously reported that STEC interaction with the human colonic mucosa enhanced Stx2 production. In the present work, we have demonstrated that infection with O157:H7∆stx2, a mutant unable to produce Stx2, enhanced either Stx2 cytotoxicity on an intestinal cell line (HCT-8) or translocation across HCT-8 monolayers. Moreover, we found that translocation was enhanced by both paracellular and transcellular pathways. Using specific endocytosis inhibitors, we have further demonstrated that the main mechanisms implicated on Stx2 endocytosis and translocation, either when O157:H7∆stx2 was present or not, were Gb3-dependent, but dynamin-independent. On the other hand, dynamin dependent endocytosis and macropinocytosis became more relevant only when O157:H7∆stx2 infection was present. Overall, this study highlights the effects of STEC infection on the intestinal epithelial cell host and the mechanisms underlying Stx2 endocytosis, cytotoxic activity and translocation, in the aim of finding new tools towards a therapeutic approach.